Kompetensi Literasi Perspektif Al-Qur’an (Studi Komparasi Mufasir Minangkabau) - Pratiwi, Agselya Putri; Taufiq, Muhammad (Lembaga Yasin AlSys, 2023)
The author limits the comparison between Minangkabau commentators on two commentators, namely Mahmud Yunus and Buya Hamka with their commentary products Tafsir Al-Qur'an Al-Karim by Mahmud Yunus and Tafsir Al-Azhar by Buya Hamka. The background of this research departs from the problem of literacy in Indonesia which is in a low class from all over the world according to a survey conducted by PISA (Program for International Student Assessment), which is in 62nd position out of 70 countries. In fact, according to statistical data, Indonesia is a country with a predominantly Muslim population. The Qur'an as the main source of religion and the life of its people has indicated a strong suggestion to form literate human character through the first prophecy received by the Prophet Muhammad. Besides that, the same social background of the two interpreters made the writer interested in examining socio-cultural values in the interpretations carried out by the two, especially in verses regarding literacy. This study uses the muqarran method (comparison/comparison) in the context of comparing the interpretations of one commentator with another. The type of this research is library research which collects data from written sources with the main sources being Tafsir Al-Qur'an Al-Karim and Tafsir Al-Azhar, and will also be supported and complemented by related written sources. such as journals, books regarding interpretation, and others. This research resulted in an understanding that there was no disagreement or significant difference in the meaning of the verses between the two commentators. While the difference between the two lies in the method of explanation used in which Mahmud Yunus chose a concise and global interpretation path, while Buya Hamka interpreted the verse with a detailed explanation and included several supporting histories to complete his interpretation. Departing from the socio-culture of the two exegetes, the writer finds the existence of cultural values in the interpretation of the two which is shown in the form of the choice of local words, the use of local expressions, and the conditions that occur locally.